Physical Intuition to Improve Electronic Properties of Thermoelectrics - Lim, Wei Yang Samuel; Zhang, Danwei; Duran, Solco Samantha Faye; Tan, Xian Yi; Tan, Chee Kiang Ivan; Xu, Jianwei; Suwardi, Ady (Frontiers in Physics, 2021)
Thermoelectrics convert heat to electricity and vice versa. They are of technological importance in cooling and energy harvesting. Their performances are defined by figure of merit, zT. Decades of studies have largely focused on the development of novel and advanced materials reaching higher performance in devices. To date, the lack of sufficiently high performance thermoelectrics, especially among Earth-abundant and light weight materials is one of the reasons why there is no broad commercial application of thermoelectrics devices yet. This challenge is due to the complex correlations of parameters that make up the zT. Theoretical estimation can reveal the optimal charge carrier concentration, which can provide a good idea of doping compositions. Depending on the material characteristics, decoupling these inter-correlated parameters could be viable. Broadly speaking, increasing carrier mobility, inducing a large fluctuation in Density-of-States (DOS) at the Fermi level, as well as lowering the lattice thermal conductivity leads to better thermoelectric performance. In this mini review, we provide a broad picture of electronic properties optimization for thermoelectric materials. This work will be a useful guide to quickly take readers to the forefront of thermoelectric research.